Efeitos da maltodextrina como aditivo via água de bebida na recepção de pintainhos submetidos a quatro períodos de jejum pós-eclosão - Machado, Camila Alves (2010)
CHAPTER 2: The objective of this research was to evaluate the effects of fasting time on bromatology carcass, biometrics organ, water intake and performance of broiler chickens. We conducted a randomized design consisting of four days of fasting after hatching (0, 12, 24 and 36 hours) and four replications. Therefore, 640 birds were distributed in sixteen boxes containing 20 females and 20 males each. Water consumption was greater the longer the duration of fasting and was greater weight loss from hatching to the accommodation. There was also the weight loss on the yolk sac. Fasting influenced the relative weight of all organs of the digestive tract except esophagus + craw that remained unchanged. With increasing fasting time increased the relative weight of the esophagus+craw, proventriculus+gizzard, intestine+ pancreas, intestine and liver+gallbladder. However, food science and animal performance were not affected by fasting. CHAPTER 3: The objective of this research was to evaluate the effect of maltodextrin on performance and biometry of the digestive organs in chicks underwent four fasting time. Was performed a completely randomized design consisting of three treatments (1 - control, 2 - 4% sugar; 3-4% maltodextrin 20) and four times of fasting after hatching (0, 12, 24 and 36 hours) with four replications , 1920 birds in total of both sexes. The results showed that both the maltodextrin as sugar stimulated the consumption of water and after 24 hours, the group that has not been pass of fasting and was approved with maltodextrin obtained with greater weight of the small intestine and pancreas, besides a greater length of the gastrointestinal tract. The performance at 42 days was not influenced by the use of additives, however, the viability suffered positive influence after seven days of life.